Molecular Identification and Phylogenetic Analysis of Ascarids in Wild Animals - Chen, Shu-Yu; Qiu, Qi-Guan; Mo, Hai-Long; Gong, Teng-Fang; Li, Fen; He, Jun-Lin; Li, Wen-Chao; Xie, Xin-Rui; Liu, Wei (Frontiers in Veterinary Science, 2022)
Ascarid nematodes are the most common and harmful nematodes parasites in animals. By analyzing genetic variation, this study explores the genetic and phylogenetic relationship among ascarids from 11 different hosts. This study collected ascarid samples from the feces of nine animal species in Changsha Ecological Zoo of Hunan Province and two animal kinds in the College of Veterinary Medicine of Hunan Agricultural University. The mitochondrial gene (pcox1) and ribosomal ITS sequences were amplified, sequenced, and analyzed by PCR to identify the species of the samples. The phylogenetic tree was constructed based on two genes (cox1 and ITS) by the Neighbor-joining method, and the phylogenetic relationship was analyzed. The sequencing results showed that the sequence lengths of pcox1 and ITS genes in the samples were 441 bp and 838–1,177 bp, respectively. The difference rates were 0.00–1.70% in pcox1 gene and 0.00–7.30% in ITS gene. Phylogenetic analysis showed that ascarid worms from the white lion, Northeast tiger, South China tiger and cheetah were identified as Toxascaris leonina. Ascarids from the zebra were identified as Parascaris equorum, while those from chicken and peacocks were identified as Ascaridia galli. Ascarids of wolf and dog origin were Toxocara canis, the snake ascarids belonged to Ophidascaris filaria, and the bear ascarids belonged to Baylisascaris transfuga. There was a significant gap between different kinds of ascarid worms. We found that these two mitochondrial genes pcox1 and ITS showed a common characteristic that the intraspecific differences were significantly smaller than the interspecific differences, confirming that these two genes could be used as interspecific genetic markers for molecular identification of different ascarids origins. The intraspecific variation rate of the ITS gene was higher than that of pcox1, indicating that ITS can also be used in the genetic research of Ascaris species development. This study revealed the genetic evolution and phylogeny of ascarids in wild animals, and our results will help prevent and control ascarids in wild animals.